Cytogenetic Monitoring in Shwachman-Diamond Syndrome. Issue 4 (May 2015) - Pressato, Barbara; Valli, Roberto; Marletta, Cristina; Mare, Lydia; Montalbano, Giuseppe; Curto, Francesco Lo; Pasquali, Francesco; Maserati, Emanuela
<x xml:space="preserve">Abstract</x> We analyzed the results of periodic chromosome analyses performed on bone marrow of 22 patients with Shwachman-Diamond syndrome (SDS), 8 directly observed and 14 from the literature, selected because of changes in the cytogenetic picture during the course of the disease. This study points out some features of the cytogenetic evolution in SDS relevant for prognostic evaluation but never noted in the literature. In particular, the lack of any clonal progression and the frequent appearance of independent clones with chromosomal changes different from the one initially discovered, with possible severe prognostic implications, are reported.